2021
DOI: 10.1021/acsami.1c05742
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening of Atomic Defects in MXenes for CO2 Capture, Activation, and Dissociation

Abstract: The capture, activation, and dissociation of carbon dioxide (CO2) is of fundamental interest to overcome the ramifications of the greenhouse effect. In this regard, high-throughput screening of two-dimensional MXenes has been examined using well-resolved first-principles simulations through DFT-D3 dispersion correction. We systematically investigated different types of structural defects to understand their influence on the performance of M2X-type MXenes. Defect calculations demonstrate that the formation of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 72 publications
1
31
0
Order By: Relevance
“…In our recent work, 76 we performed high-throughput screening to understand the CO 2 capture and activation mechanism over a series of bare and defective M 2 X-type MXenes. We observed remarkably high adsorption energies and charge transfer from group IV (Ti 2 X and Zr 2 X) MXenes to CO 2 molecules, followed by dissociation into CO and O species.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent work, 76 we performed high-throughput screening to understand the CO 2 capture and activation mechanism over a series of bare and defective M 2 X-type MXenes. We observed remarkably high adsorption energies and charge transfer from group IV (Ti 2 X and Zr 2 X) MXenes to CO 2 molecules, followed by dissociation into CO and O species.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the perfect sites interact nonspontaneously with CO 2 via an endothermic process. 245 Our recent studies 264 on defective MXenes demonstrate unprecedented high adsorption energies and charge transfer from M 2 X to CO 2 for group IV based M 2 X systems as shown in Fig. 8f-i.…”
Section: Mxenes For Co 2 Conversionmentioning
confidence: 87%
“…Singh et al 205 systematically screened the different types of atomic defects on M 2 X-type MXenes. They found that higher energy was required for the formation of M 2 C(V MC ) and M 2 N(V MN ) vacancies, while the formation of the M 2 C(V C ) and M 2 N(V N ) vacancies is preferable on M 2 X-type MXenes, as shown in Fig.…”
Section: Prediction Of Defect Formationmentioning
confidence: 99%